Bitemporal data : theory and practice - Johnston, Tom (Waltham, MA : Morgan Kaufmann, 2014)
Bitemporal data is coming, and major database management systems are beginning to support it. You need to know what is going on ""under the hood"" and this book that will make you the expert on bitemporal data that every IT organization should have on its staff. There''s a lot more to bitemporal data than adding a second timestamp to history tables: for example, a temporal update of a single customer in a bitemporal customer table could require up to a dozen physical SQL transactions to complete. Vendors will eventually make it possible to write bitemporal transactions and bitemporal queri.
Whenever Temporal TransactionsTemporal Merge Transactions; Glossary List; Chapter 12. Basic Temporal Queries; Temporal Query Syntax; Bitemporal Tables and Views; Point-In-Time Range Queries; Range Queries; Glossary List; Chapter 13. Advanced Temporal Queries; A Basic Temporal Range Multi-Table Query; A Complex Temporal Range Multi-Table Query; Why Temporal Range Multi-Table Queries are Complex; Glossary List; Chapter 14. Future Assertion Time; Future Assertion Time: Semantics; Future Assertion Time: Implementation; Glossary List; Chapter 15. Temporal Requirements.
Print version record.
Includes bibliographical references and index.
Keywords: Temporal databases; Database management; COMPUTERS -- Database Management; Database management; Temporal databases; Electronic books